The took typology: approaches analysis and the direction of development - E. V. Sautina (Библиосфера)
The problem of book typology being of decisive importance to identify the essential properties of a book as an object of communication is examined. The paper analyzes existing in bibliology concepts of book typology, their advantages and disadvantages, and determines the future research directions of book typological characteristics. Bibliological papers identify the important role of the typology in studying the essential book characteristics, formulate conditions of effective typologization and principles forming the typological book structure basis, designate methodological approaches to the criterion based on which the book typologization is possible. There are logical and methodological shortcomings in typological constructions made on the base of these regulations, which could be eliminated by studying the book in frames of the whole documentative system, i. e. as a document type. This approach will make it possible to determine the essential features of the book distinguishing it from other types of documents, accounting the modern conditions of communication.